Kaposi’s sarcoma in AIDS patients: a case series - Dominiak, Małgorzata; Domurad-Falenta, Julia; Lesiak, Aleksandra; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2024)
Kaposi’s sarcoma is a multifocal tumor of endothelial origin associated with human herpesvirus 8 infection. Lesions typically appear as patches, plaques, or hemorrhagic nodules. Kaposi’s sarcoma occurs in four main forms: classic, endemic African, iatrogenic (linked to immunosuppressive therapy), and epidemic (associated with HIV infection). In HIV-infected patients, lesions commonly affect the face and may spread to the limbs, trunk, and genital areas. In some cases, internal organs, primarily the gastrointestinal tract, may also be involved. The diagnosis of Kaposi’s sarcoma requires histopathological confirmation. Early detection and prompt initiation of antiretroviral therapy are crucial for improving patient prognosis.